Apakah Agama Hindu Bali Modern Lahir dari Tantangan Pancasila dan Islam - Nyoman Wijaya (Pusat Kajian Bali Universitas Udayana, 2014)
AbstractThe existence of Hinduism in Bali and generally inIndonesia gained recognition by the state as the official religion through a complicated process. This article will answer the question in the title above to see pemaskaraan (polishing) process and replicate the Balinese religion. The purpose of pemaskaraan (polishing) in order to enhance his form of religion and culture in order to lookmore beautiful than the original. Pemaskaraan (polishing)process is detected when the organic intellectuals manage their fear of the religions of non-Hindu in an effort to maintain the authenticity of Bali. Pemaskaraan (polishing) Balinese religion, emerged as organic intellectuals reaction against the widespread threats of religious conversion in Bali. Pemaskaraan (polishing) realized by smoothing the basis of the Hindu religion.And replication is the impersonation of religion of the majority, so the Balinese religion is not alienated in the society of nation and state.